Akibat Hukum Money Politic dalam Hukum Positif - Diningrat, A.A.A. Putri Dwi; Saravistha, Deli Bunga; Suputra , I Wayan Darmika (Indra Institute Research & Publication, 2024)
In general, general elections are conducted by a legitimate state in order to select a leader for the nation (a political position). Legislative regulations govern the procedures for holding elections, but some candidates use money politics to gain an advantage over their rivals. To genuinely be in line with the essence of money politics, money politics actions need to be carefully thought out. Legal studies must substantiate the practice of substituting transportation, fatigue, and food funds for voter mobilization in public campaigns. The use of criminal law as a last resort must be thoroughly examined, as well as the legal tools for preventing money politics. A number of additional strategies can. The recognition and assertion of the rule of law, along with the placement of the law as the supreme command in state administration, imply that all facets of government administration, including the regulation of general elections (Elections), are subject to stringent legal frameworks and legislative regulations. Election procedures must adhere to certain principles, including those of direct, general, free, secret, honest, and fair. Though in this instance the author focuses more on the application of the principles of honesty and fairness, the author believes that these five values have a similar role in developing officials with high integrity. Since it is commonly known that throughout the several elections that have taken place since they were first conducted in 1955 till the present Money politics is the area where election violations occur most frequently. Money politics is prohibited by legal instruments (criminal legal instruments), and there are two ways to deal with political violations: the police can impose administrative sanctions or criminal penalties. The issues brought up in this article are as follows, based on the introduction: first, how is money politics regulated by positive law? Secondly, how successful are the legal tools available to stop money politics, and what cultural countermeasures are there?